HPA axis stress reactivity and hair cortisol concentrations in recently detoxified alcoholics and healthy controls with and without childhood maltreatment - Mühlhan, Markus; Höcker, Anja; Miller, Robert; Trautmann, Sebastian; Wiedemann, Klaus; Lotzin, Annett; Barnow, Sven; Schäfer, Ingo (Addiction biology, 2020)
Childhood maltreatment (CM) is a strong risk factor for alcohol dependence (AD) and is associated with a more severe course of the disease. Alterations of the hypothalamic-pituitary-adrenal (HPA) axis may play an important role in this relationship. The aim of the present study was to systematically investigate potential alterations in HPA functioning associated with AD diagnosis and CM. Four study groups were recruited: AD patients with (n = 29; 10♀) and without (n = 33; 8♀) CM and healthy controls with (n = 30; 20♀) and without (n = 38; 15♀) CM. Cumulative cortisol secretion was measured by hair cortisol concentration (HCC). To measure HPA axis response to the Trier social stress test (TSST), saliva and blood samples were analysed for adrenocorticotropic hormone (ACTH) and cortisol. In the AD groups, the period of hair growth covered acute alcohol consumption and withdrawal. The TSST was scheduled after completion of withdrawal. Irrespective of CM, higher HCCs and reduced ACTH and cortisol levels before and after TSST were observed in AD patients. The analyses did not reveal any differences between AD patients with and without CM. Healthy controls with CM had lower plasma cortisol levels compared with those without CM. The results suggest that AD is strongly related to HPA axis functioning, which may superimpose possible differences between AD patients with and without CM. Future studies should investigate whether biologically different subtypes of AD with and without CM can be identified in earlier stages or before the development of AD.
Gesehen am 05.10.2020
First published: 11 October 2018